(untitled) (Damu Journal of Sport Sciences, 2024)
Standards are a characteristic of modernity, which necessitated studying the important factors in advancement in this lesson in order to reach the ranks of developed countries. The problem of the research was: Is there a relationship between the objectives of the physical education lesson and the comprehensive quality standards in middle schools in the Babylon Governorate Center from the point of view of the physical education teachers in the Babylon Governorate Center, and what is the contribution rate of the comprehensive quality standards to those objectives? The most important objectives of the research are to identify the percentage of contribution of comprehensive quality standards to achieving the objectives of the physical education lesson for the preparatory stage from the perspective of physical education teachers in Babylon. Comprehensive quality standards contribute to achieving the objectives of the physical education lesson for the preparatory stage in Babylon. . The research population was representative of the sample and amounted to 104 teachers. After confirming the scientific foundations of the exploratory experiment, conducting the main experiment, and analyzing the data for correlation and contribution rates, the researcher reached the most important conclusions. There were contribution rates for each of the following: Comprehensive quality standards based on the objectives of the physical education lesson for the preparatory stage. The most important recommendations are adopting comprehensive quality and sustainable development standards in achieving the objectives of the physical education lesson.